Adsorption Studies of Methylene Blue and Methylene Red on Activated Carbon Derived from Agricultural waste: Rubber (Havea brasiliensis) Seed Powder - Eko Ariyanto (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Activated carbon prepared from rubber (Havea brasiliensis) seeds was used to remove methylene blue and methyl red from aqueous solutions. Adsorption studies were conducted to evaluate the effect of contact time and amount of carbon active on the removal of methylene blue and methyl red at temperature of 25oC. The equilibrium adsorption data of methylene blue and methyl red on activated carbon were analyzed by Freundlich and Langmuir isotherm model. The absorption kinetic models were predicted by pseudo-first-order and pseudo-second-order. The pseudo-second-order kinetic model was the best fitting equilibrium adsorption data. The results of adsorption methylene blue and methyl red on aqueous solutions shown that rubber seeds as carbon active can be used as material for adsorption.